Search for WW and WZ production in lepton plus jets final state at CDF - Aaltonen, T; Adelman, J; Akimoto, T; Alvarez Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2009)
We present a search for WW and WZ production in final states that contain a charged lepton (electron or muon) and at least two jets, produced in s=1.96TeV pp̄ collisions at the Fermilab Tevatron, using data corresponding to 1.2fb-1 of integrated luminosity collected with the CDF II detector. Diboson production in this decay channel has yet to be observed at hadron colliders due to the large single W plus jets background. An artificial neural network has been developed to increase signal sensitivity, as compared with an event selection based on conventional cuts. We set a 95% confidence level upper limit of σWW×BR(W→ν,W→jets)+σWZ×BR(W→ ν ,Z→jets)<2.88pb, which is consistent with the standard model next-to-leading-order cross section calculation for this decay channel of 2.09±0.12pb. © 2009 The American Physical Society.